Promoting healthy eating in Latin American restaurants: a qualitative survey of views held by owners and staff - Melissa Fuster; Rosa Abreu-Runkle; Margaret A. Handley; Donald Rose; Michelle A. Rodriguez; Emily G. Dimond; Brian Elbel; Terry T. K. Huang (BMC, 2022)
Abstract Background Restaurants, particularly independently-owned ones that serve immigrant communities, are important community institutions in the promotion of dietary health. Yet, these restaurants remain under-researched, preventing meaningful collaborations with the public health sector for healthier community food environments. This research aimed to examine levels of acceptability of healthy eating promotion strategies (HEPS) in independently-owned Latin American restaurants (LARs) and identify resource needs for implementing HEPS in LARs. Methods We completed semi-structured, online discussions with LAR owners and staff (n = 20), predominantly from New York City (NYC), to examine current engagement, acceptability, potential barriers, and resource needs for the implementation of HEPS. Verbatim transcripts were analyzed independently by two coders using Dedoose, applying sentiment weighting to denote levels of acceptability for identified HEPS (1 = low, 2 = medium/neutral, 3 = high). Content analysis was used to examine factors associated with HEPS levels of acceptability and resource needs, including the influence of the Coronavirus pandemic (COVID-19). Results The most acceptable HEPS was menu highlights of healthier items (mean rating = 2.8), followed by promotion of healthier items (mean rating = 2.7), increasing healthy offerings (mean rating = 2.6), nutrition information on the menu (mean rating = 2.3), and reduced portions (mean rating = 1.7). Acceptability was associated with factors related to perceived demand, revenue, and logistical constraints. COVID-19 had a mixed influence on HEPS engagement and acceptability. Identified resource needs to engage in HEPS included nutrition knowledge, additional expertise (e.g., design, social media, culinary skills), and assistance with food suppliers and other restaurant operational logistics. Respondents also identified potential policy incentives. Conclusions LARs can positively influence eating behaviors but doing so requires balancing public health goals and business profitability. LARs also faced various constraints that require different levels of assistance and resources, underscoring the need for innovative engagement approaches, including incentives, to promote these changes.